Glufosinate, nicosulfuron and combinations in the performance of maize hybrids with the pat gene - Wehrmeister, Rafael (Revista Ciência Agronômica, 2021)
Combinations of glufosinate with nicosulfuron, among other post-emergent herbicides, are promising for weed controlin maize. However, some of these herbicides can cause injury and have other undesirable effects on the maize, so it is necessaryto investigate their selectivity for cultivation. The aim of this study was to evaluate the selectivity of glufosinate, nicosulfuron andcombinations, by analysing the agronomic performance of the crop for post-emergent application in maize hybrids with the pat gene.Two experiments were conducted in the state of Paraná, Brazil, during the 2019/2020 season, in a 2 x 8 (exp. I) and 2 x 4 (exp. II)factorial scheme. Two hybrids were used (FS505 PWU and FS715 PWU), with eight levels for the factor herbicide in experiment I(glufosinate, halosulfuron and glufosinate in combination with halosulfuron, nicosulfuron, atrazine, tembotrione or mesotrione, inaddition to the control with no application) and four levels of herbicide in experiment II (nicosulfuron in two formulations, mesotrione,and the control). Injury to the maize plants and variables related to agronomic performance were evaluated. Although the herbicideshad no effect on yield, it can be inferred that FS505 is more sensitive to nicosulfuron and mesotrione than is FS715, since the injurywas greater than seen in FS715. The post-emergent application of glufosinate, nicosulfuron and combinations is selective for the FS505PWU and FS715 PWU hybrids (with the pat gene). Despite injury, which was more pronounced in the FS505 PWU hybrid, there wasno negative impact on yield or on other the variables of agronomic performance.